COVID-19 Vaccine in Immunosuppressed Adults with Autoimmune rheumatic Diseases (COVIAAD): safety, immunogenicity and antibody persistence at 12 months following Moderna Spikevax primary series - Emmanouil Rampakakis; Paul R Fortin; Sasha Bernatsky; Louis Bessette; Ines Colmegna; Elizabeth Hazel; Laëtitia Michou; Mary-Ann Fitzcharles; Louis Flamand; Emmanuelle Rollet-Labelle; Marc-André Langlois; Valeria Valerio; et al. (RMD Open, 2023)
Objective To assess the safety, immunogenicity and cellular responses following the Moderna Spikevax primary series in rheumatic disease.Methods We conducted a 12-month, prospective, non-randomised, open-label, comparative trial of adults with either rheumatoid arthritis (RA, n=131) on stable treatment; systemic lupus erythematosus (SLE, n=23) on mycophenolate mofetil (MMF); other rheumatic diseases on prednisone ≥10 mg/day (n=8) or age-matched/sex-matched controls (healthy control, HC, n=58). Adverse events (AEs), humoral immune responses (immunogenicity: IgG positivity for anti-SARS-CoV-2 spike protein and its receptor binding domain, neutralising antibodies (NAbs)), cellular responses (ELISpot) and COVID-19 infection rates were assessed.Results Frequency of solicited self-reported AEs following vaccination was similar across groups (HC 90%, RA 86%, SLE 90%); among them, musculoskeletal AEs were more frequent in RA (HC 48% vs RA 66% (Δ95% CI CI 3 to 32.6)). Disease activity scores did not increase postvaccination. No vaccine-related serious AEs were reported. Postvaccination immunogenicity was reduced in RA and SLE (RA 90.2%, SLE 86.4%; for both, ΔCIs compared with HC excluded the null). Similarly, NAbs were reduced among patients (RA 82.6%, SLE 81.8%). In RA, age >65 (OR 0.3, 95% CI 0.1 to 0.8) and rituximab treatment (OR 0.003, 95% CI 0.001 to 0.02) were negative predictors of immunogenicity. ELISpot was positive in 16/52 tested RA and 17/26 HC (ΔCI 11.2–53.3). During the study, 11 HC, 19 RA and 3 SLE patients self-reported COVID-infection.Conclusion In COVID-19 Vaccine in Immunosuppressed Adults with Autoimmune Diseases, the Moderna Spikevax primary series was safe. MMF, RA age >65 and rituximab were associated with reduced vaccine-induced protection.